1998
DOI: 10.1243/0954410981532270
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent rotating flow calculations: An assessment of two-equation anisotropic and Reynolds stress models

Abstract: The stress field in a rotating turbulent internal flow is highly anisotropic. This is true irrespective of whether the axis of rotation is aligned with or normal to the mean flow plane. Consequently, turbulent rotating flow is very difficult to model. This paper attempts to assess the relative merits of three different ways to account for stress anisotropies in a rotating flow. One is to assume an anisotropic stress tensor, another is to model the anisotropy of the dissipation rate tensor, while a third is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…When the same authors (Chen and Lin, 1999) modelled the Kitoh (1991) swirling flow, the SSG model performed better, however, the centreline backflow was still difficult to model especially far downstream. Similar difficulties with the SSG model and variants were also experienced by Yuan and So (1998). Yeh and Lin (2000) and Lu and Semião (2003) found that for strongly swirling flows the SSG model predicted slightly better results than the linear pressure-strain models.…”
Section: Slow Pressure-strain Term Ij 1supporting
confidence: 52%
See 3 more Smart Citations
“…When the same authors (Chen and Lin, 1999) modelled the Kitoh (1991) swirling flow, the SSG model performed better, however, the centreline backflow was still difficult to model especially far downstream. Similar difficulties with the SSG model and variants were also experienced by Yuan and So (1998). Yeh and Lin (2000) and Lu and Semião (2003) found that for strongly swirling flows the SSG model predicted slightly better results than the linear pressure-strain models.…”
Section: Slow Pressure-strain Term Ij 1supporting
confidence: 52%
“…This occurred because of a number of reasons: (1) the near wall velocities and therefore the shear stresses were predicted correctly, and (2) the swirl number is the ratio of two integrals which have a higher weighting in the correctly predicted annular and near wall regions. Good swirl number matches with poor recirculation zone predicted velocity profiles were also found by Yuan and So (1998) when they compared their simulated results with the experiments (S = 0.97) of Kitoh (1991). Alekseenko et al (1999) also found during their experiments that the swirl number was not a unique parameter by which quite different swirling flow structures can be characterised.…”
Section: Swirl Numbermentioning
confidence: 70%
See 2 more Smart Citations